Enhanced peroxymonosulfate activation by Co-bHAP catalyst for efficient degradation of sulfamethoxazole. Issue 2 (April 2023) - Tong, Qibang; Li, Congyi; Wang, Guixin; Wang, Yao; Peng, Shuo; Wang, Jihang; Lai, Bo; Guo, Yong
Abstract: The abuse of antibiotics has drawn wide attention owing to their potential risk in human health and ecosystem. As one of the most commonly used sulfonamide antibiotics, sulfamethoxazole (SMX) can hardly be removed by conventional wastewater treatment methods, and thus it has become one of the most frequently detected antibiotics in water environment. In this study, a new cobalt-based heterogeneous catalyst (Co-bHAP) was successfully prepared using the simple impregnation method with animal bone-derived hydroxyapatite (bHAP) as the support, and applied to activate peroxymonosulfate (PMS) for the degradation of SMX in water. The physicochemical properties of Co-bHAP catalyst were investigated by series of characterization methods, and the results showed that this catalyst has a rough and porous morphological structure, as well as homogeneously distributed active component, which is mainly in the form of Co3 O4 . The developed Co-bHAP can provide abundant reaction active sites and exhibit excellent catalytic activity and stability in PMS activation. The kinetic constant of Co-bHAP activating PMS to degrade SMX is up to 0.1524 min −1, which is 4.5 times larger than that of bare Co3 O4 . The SMX (20 mg/L) degradation efficiency within 30 min in Co-bHAP/PMS system reached as high as 98.7% and still maintained at 86% after 5 times consecutive operation, with slight cobalt ions leaching less than 0.1 mg/L. Based on radical quenching experiment, electron paramagnetic resonance (EPR) test and XPS analysis, the reaction mechanism was proposed. The balance among Co 3+ /Co 2+, O 2− /O2 and PMS decomposition in Co-bHAP/PMS system ensured the continuous generation of sulfate radical (SO4 – ) and hydroxyl radical (HO ), both of which are responsible for SMX degradation, while SO4 – plays a leading role. In addition, four possible pathways of SMX degradation were proposed according to the eight detected intermediate products. All the results suggested that this catalyst could have a promising potential in activating PMS to degrade sulfonamide antibiotic pollutants in water. Graphical Abstract: ga1 Highlights: Co-bHAP catalyst was successfully prepared using porous animal-bone-derived HAP as support. Co-bHAP exhibited excellent catalytic activity and stability in PMS activation. SO4 – and HO were responsible for SMX degradation in Co-bHAP/PMS system. The degradation efficiency of SMX reached as high as 98.7%.